Motivational profiles and learning experience across Chinese language proficiency levels. (June 2020) - Wen, Xiaohong; Piao, Meiyu
Abstract: This study examines how the Ideal self and the Ought-to self impact learning, and how future self-guides sustain L2 Chinese learning. Twenty college CFL students at three proficiency levels participated in two rounds of interviews to self-identify aspects of their motivation and motivational experience over a period of one semester. All interviews were recorded and transcribed for analysis. The results demonstrated that motivation factors that sustained Chinese language learning encompassed three dimensions: The ideal L2 self/intrinsic motivation, instrumentality, and future self-guides that triggered individual self-regulatory strategies. In addition, instrumentality and obligations transitioned from the ought-to self to the ideal L2 self in the learning process. The participants' persistent desire to function in Chinese and retrospective assessments of their learning needs and styles guided them through their learning. When confronted with difficult situations, they monitored and readjusted based on their learning strengths and goals. Lastly, positive self-concept-related motivation interacted with learning experience, which reacted to adversities in context.